Determinants of knowledge and attitudes toward Mpox among medical students: A cross-sectional study from Kurdistan region of Iraq - Ibrahim A. Naqid; Ahmed A. Mosa; Nawfal R. Hussein; Iman Haji Yaseen; Kareen Yarwant Naisan; Israa Taher Shuker; Sidra Anwar Kadhim; Aveen Saleem Shareef; Mina A. Almohammed (PLoS ONE, 2026)
Introduction and Objectives Mpox is a re-emerging zoonotic viral infection that has recently caused widespread outbreaks in previously non-endemic regions, becoming an international public health concern. Medical students are future healthcare workers (HCWs); they play a critical role in public health initiatives and targeted preventive measures. Therefore, it’s necessary to assess and enhance their knowledge and attitude concerning new emerging infectious diseases like Mpox. Therefore, in this study, we aimed to fill the literature gap by assessing medical students’ knowledge and attitudes regarding Mpox infection in the Kurdistan Region of Iraq. Additionally, the study intends to demonstrate a correlation between knowledge and attitudes levels and demographic characteristics. Materials and Methods This cross-sectional study was carried out in Duhok Province, Kurdistan Region, Iraq, from January 30, 2024, to April 4, 2024, involving a total of 330 medical students. Data were collected using a structured self-administered questionnaire comprising 36 items categorized into three distinct sections: demographic characteristics, knowledge, and attitude. To maximize the response rate, both digital questionnaires distributed via Google Forms and traditional paper-based formats were employed. Results The participants’ mean age was 21.57 ± 1.69 years, with a slight female predominance (52.12%). Only (8.18%) of students had received Mpox training program. Social media was the primary information source for (36.97%) of students. The median [IQR] scores for knowledge and attitude were 20 [16 –23], and 42 [37 –45], respectively. About (40.91%) of respondents exhibited good knowledge, while (47.88%) demonstrated a positive attitude. A better knowledge score was significantly associated with age (p = 0.0067), and prior awareness of smallpox (p = 0.0011). In contrast, students who relied on friends as the main source of Mpox information demonstrated significantly lower knowledge levels (p = 0.015). Attitude was significantly linked to gender (p = 0.012), and a history of chickenpox (p = 0.0019). Conclusion Medical students in the present study demonstrated relatively insufficient knowledge about Mpox. However, their attitudes were more favorable, albeit still suboptimal. These findings highlight the urgent necessity for structured educational programs on emerging infectious diseases for health sciences students, with prioritization of students lacking knowledge of smallpox and chickenpox, and those who depended on non-formal information sources. Such programs are essential to equip students with the necessary knowledge and skills to enhance their ability to respond to and control infectious diseases outbreaks.